Adipocytes orchestrate the formation of tertiary lymphoid organs in the creeping fat of Crohn's disease affected mesentery. (September 2019) - Guedj, Kevin; Abitbol, Yaël; Cazals-Hatem, Dominique; Morvan, Marion; Maggiori, Léon; Panis, Yves; Bouhnik, Yoram; Caligiuri, Giuseppina; Corcos, Olivier; Nicoletti, Antonino
Abstract: The formation of tertiary lymphoid organs (TLOs) is orchestrated by the stromal cells of tissues chronically submitted to inflammatory stimuli, in order to uphold specific adaptive immune responses. We have recently shown that the smooth muscle cells of the arterial wall orchestrate the formation of the TLOs associated with atherosclerosis in response to the local release of TNF-α. Observational studies have recently documented the presence of structures resembling TLOs the creeping fat that develops in the mesentery of patients with Crohn's disease (CD), an inflammatory condition combining a complex and as yet not elucidated infectious and autoimmune responses. We have performed a comprehensive analysis of the TLO structures in order to decipher the mechanism leading to their formation in the mesentery of CD patients, and assessed the effect of infectious and/or inflammatory inducers on the potential TLO-organizer functions of adipocytes. Quantitative analysis showed that both T and B memory cells, as well as plasma cells, are enriched in the CD-affected mesentery, as compared with tissue from control subjects. Immunohistochemistry revealed that these cells are concentrated within the creeping fat of CD patients, in the vicinity of transmural lesions; that T and B cells are compartmentalized in clearly distinct areas; that they are supplied by post-capillary high endothelial venules and drained by lymphatic vessels indicating that these nodules are fully mature TLOs. Organ culture showed that mesenteric tissue samples from CD patients contained greater amounts of adipocyte-derived chemokines and the use of the conditioned medium from these cultures in functional assays was able to actively recruit T and B lymphocytes. Finally, the production of chemokines involved in TLO formation by 3T3-L1 adipocytes was directly elicited by a combination of TNF-α and LPS in vitro . We therefore propose a mechanism in which mesenteric adipocyte, through their production of key chemokines in response to inflammatory/bacterial stimuli, may orchestrate the formation of functional TLOs developing in CD-affected mesentery. Graphical abstract: Image 1 Highlights: TLOs develop in the CD's mesenteric adipose tissue facing intestinal lesions. TLOs support local GC B cell responses. Inflammatory/bacterial stimuli triggered chemokine production by adipocytes. 'Organizer' adipocytes could thereby orchestrate TLO formation. Monitoring TLOs could be used to stage CD. Targeting TLOs may become a strategy to impact on the pathologic process of CD.